Assessment of heterosis and inbreeding depression for agro-morphological traits in bread wheat - Kumar, Pradeep; Nagar, Satnam Singh; Singh, Charan; Gupta, Vikas; Singh, Gyanendra; Tyagi, BS (Journal of Cereal Research, 2019)
A study was conducted for the assessment of heterosis and inbreeding depression for grain yield and its contributing traits in bread wheat using a 13 × 13 diallel fashion excluding reciprocals. The analyses of heterosis over mid parent (MP), better parent (BP) as well as the standard check (SC; NW 1014) were carried out in 78 F1 and F2 crosses and inbreeding depression in F2 crosses. Biological yield exhibited maximum degree of SC, BP and MP heterosis (46.96%, 39.98% and 31.78%), followed by grain yield (35.27%, 27.58% and 20.52%), respectively. The crosses viz., PBW 343 × HI 1563 (PH, ET, TGW, BY); PBW 343 × K 8962 (PH, ET, SPS, GNPS, TGW, BY); RAJ 3765 × UP 2490 (PH, SL, SPS, GNPS, TGW, BY); UP 2490 × CBW 38 (SL, ET, SPS, GNPS, TGW, BY) and NW 2036 × UP 2490 (SPS, GNPS, TGW, BY) expressed significant standard heterosis (>50%) for grain yield and some other yield components. All these crosses had significant performance in both generations (F1 and F2) hence, can be exploited for the development of high yielding lines and/or isolation of desirable transgressive segregants. Thus these crosses combinations may be used for developing superior genotypes. The crosses viz., PBW 343 × RAJ 3765 (-26.17), RAJ 3765 × HP 1744 (-20.66), NW 1014 × CBW 38 (-19.95), RAJ 3765 × CBW 38 (-10.31), HP 1744 × CBW 38 (-9.71) and UP 2425 × CBW 38 (-5.87) express negative significant inbreeding depression for grain yield and also exhibited >15% heterosis over three parents, indicating non-additive type of gene action in the inheritance of these characters and therefore these crosses could be used for further improvement of grain yield in bread wheat. DOI.org/ 10.25174/2249-4065/2019/89648